2018
DOI: 10.1371/journal.pone.0204424
|View full text |Cite
|
Sign up to set email alerts
|

Is psychological stress a predisposing factor for amyotrophic lateral sclerosis (ALS)? An online international case-control study of premorbid life events, occupational stress, resilience and anxiety

Abstract: Psychological stress has been suggested to be relevant to the pathogenesis of neurodegenerative disorders, possibly via the generation of oxygen free radicals. We therefore sought to determine whether people with amyotrophic lateral sclerosis (ALS) had been subjected to more potentially stressful life events or occupations than controls, and whether they had differences in resilience or trait anxiety that would moderate their responses to these stressors. An online anonymous multilingual questionnaire was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…In the current study, elevated risks were associated with having experienced more than two different types of traumatic life events, with an almost twofold risk associated with having experienced four or more types of traumatic life events. An Australian ALS case–control study, 30 which used a checklist for potentially stressful life events as part of an anonymous online questionnaire, found no difference in life events inventory scores between cases and controls, but results for specific traumatic life events were not presented. We are not aware of other studies that evaluated the association between traumatic life events and MND.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, elevated risks were associated with having experienced more than two different types of traumatic life events, with an almost twofold risk associated with having experienced four or more types of traumatic life events. An Australian ALS case–control study, 30 which used a checklist for potentially stressful life events as part of an anonymous online questionnaire, found no difference in life events inventory scores between cases and controls, but results for specific traumatic life events were not presented. We are not aware of other studies that evaluated the association between traumatic life events and MND.…”
Section: Discussionmentioning
confidence: 99%
“…A Japanese case–control study 13 showed that self‐reported stress was associated with an increased risk of ALS (OR 1.8, 95% CI 1.3–2.7) while a UK study 29 reported a 1.5‐fold increased MND risk for a former diagnosis of depression. However, a recent Australian study 30 found no difference in exposures to potentially stressful life events between ALS cases and controls.…”
Section: Introductionmentioning
confidence: 91%
“…This suggestion could also lead to hypothesizing a correlation between mitochondrial dysfunction and excessive stress [28]. However, a recent study showed that people with ALS reported no raised levels of potentially stressful premorbid life events or occupational stress and did not have reduced levels of resilience [29]. Therefore, a possible role of exceptional physical or psychological stress (at least by itself) in the pathogenesis of ALS is still an open question.…”
Section: Mitochondrial Dysfunction At the Core Of Als Pathophysiologymentioning
confidence: 99%
“…Epidemiological studies support that stress exposure, including everyday life stress, work stress, life events, and trauma, is associated with dementia risk, whereas results for PD have been inconsistent . The potential association between stressful life events and amyotrophic lateral sclerosis (ALS) was not supported in 2 previous studies, but this association is underexplored to date.…”
Section: Introductionmentioning
confidence: 99%